Implementasi CRM (Customer Relationship Management) Berbasis Website pada Angkasa Photo Studio Tanjungpinang - Mochammad Rizki Romdoni; Lia Rosanty; Liza Safitri; Aggry Saputra (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
Angkasa Photo Studio is a company engaged in photography services that offers a variety of products such as photo studios, graduations, family, documentation, weddings, products and others. In carrying out its activities, Angkasa Photo Studio requires an information system software whose use is to establish maximum communication with consumers and strive for continuous sales to them to increase company income such as CRM (Customer Relationship Management). Especially in recent years the Covid-19 pandemic has certainly greatly disrupted people's mobility, especially in obtaining information about the marketing of goods and services. After the research, there were problems, namely a decline in sales due to the Covid-19 pandemic and in carrying out marketing activities they still applied conventional methods and there was no system to establish maximum communication with consumers. Based on these problems, the researcher tries to design a website-based CRM system that can identify customer satisfaction with Angkasa Photo Studio's services. In designing this system using the PHP programming language and using Mysql as a database. After the researcher succeeded in designing a website-based CRM system at Angkasa Photo Studio, the results showed that the system designed was able to identify consumer satisfaction with Angkasa Photo Studio services, was able to establish more optimal communication with customers, and the system was able to market products and promos and customers did not need to come. Visit the store to find out what products and promos are currently available